Implementation of Thin Layer Chromatography to Detect Dihydroxybenzene Isomers for Cosmetic Product Regulatory Enforcement - Hasibuan, Anggi Khairina Hanum; Permatasari, Novita Indah (Indonesian Journal of Chemical Studies, 2022)
Thin Layer Chromatography (TLC), used in forensic analysis, has many advantages: simple, cheap, and efficient. This study aimed to separate dihydroxybenzene isomers in whitening creams in the market and online shops using the BPOM label or not. Of the six eluent mixtures, this research used Toluene: Diethyl Ether: Acetic Acid with a ratio of 80:20:1 after optimization and validation test. In this case, the recovery percentages of resorcinol and hydroquinone were 51-66% and 80-87%. Of the 20 samples tested, 12 whitening creams were added with resorcinol, and 4 were added with hydroquinone. The addition of resorcinol and hydroquinone based on the regulation in Perka BPOM no 18 of 2015 was 5%. Furthermore, 2 out of 20 samples were added with hydroquinone within the regulated threshold, while the remaining 2% were accepted and the other six were undetected. In this case, adding hazardous substances has violated the rules of consumer protection laws and regulations.